Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica - ROMERO, DAVID (2018)
A new species of Moribaetis is described based on nymphs from the Nicoya peninsula. The new species can be distin guished from the other described species of the genus, among other characteristics, by its short antennae, strongly curved lateral branches of the epicranial suture, long mandibular incisors projected beyond labrum margin, violet-colored gills, and a distinctive triangular projection on paraproct. Moribaetis brachiostrinus, M. macaferti and M. salvini share certain characters that set them apart from M. maculipennis suggesting that the latter represents a separate branch within this ge nus. M. brachiostrinus has the lowest altitudinal distribution of the genus in Costa Rica and represents the first record of a Moribaetis occurring on the oldest emerged lands in the country. Comments on the age-related changes in the mandibular incisors and a key to mature nymph of Moribaetis species are also provided